2021
DOI: 10.3390/nu13051484
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Effects of Fruit Pulps from the Amazon Biome on Physiological Parameters in Rats

Abstract: This study aimed to analyze the physicochemical characteristics and the effects of Amazonian pulp fruits consumption, such as araçá-boi (Eugenia stipitata), abiu grande (Pouteria caimito), araticum (Annona crassiflora), biri-biri (Averrhoa bilimbi L.), and yellow mangosteen (Garcinia xanthochymus), on hematologic, metabolic, renal, and hepatic function parameters in Wistar rats (n = 10 rats/group). The pulp of abiu had the highest levels of soluble solids, sugars, and pH. Biri-biri pulp had the highest levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In addition to antioxidant effects, some extracts, fractions, or isolated compounds from araticum fruit, particularly from the peel, also presented anti-inflammatory activity ( Table 2 ). Daily intake of whole araticum pulp (3.214 mL/kg bw) for 30 days promoted a significant reduction in the total leukocytes of rats as compared to the control group [ 57 ]. Justino et al [ 56 ] evaluated the effect of different ethanolic extract fractions from araticum peel on pro-inflammatory mediators’ production in an LPS-induced macrophage model.…”
Section: Biological Activities Reported In Araticum Fruit Partsmentioning
confidence: 99%
“…In addition to antioxidant effects, some extracts, fractions, or isolated compounds from araticum fruit, particularly from the peel, also presented anti-inflammatory activity ( Table 2 ). Daily intake of whole araticum pulp (3.214 mL/kg bw) for 30 days promoted a significant reduction in the total leukocytes of rats as compared to the control group [ 57 ]. Justino et al [ 56 ] evaluated the effect of different ethanolic extract fractions from araticum peel on pro-inflammatory mediators’ production in an LPS-induced macrophage model.…”
Section: Biological Activities Reported In Araticum Fruit Partsmentioning
confidence: 99%
“…Thus, the different extractor solvents used in the studies can, at least partially, explain the different values of total phenolic content found [ 31 ]. However, several studies used the same conditions to extract phenolic compounds from araticum pulp (successive extraction using 50% methanol and 70% acetone) and obtained discrepant results (total phenolic content values ranging from 2.22 to 10.08 mg GAE/g fw) [ 9 , 10 , 25 , 26 , 27 , 28 , 29 ]. Therefore, other factors such as geographical and environmental conditions of the fruit’s origin region (e.g., temperature, soil, incidence and intensity of light, harvest time, among others), physiological and genetic factors of the plant, and sample preparation and storage conditions may be associated with the observed variations in total phenolic values among studies [ 14 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this fruit has been used for centuries in local and traditional medicine as a tonic and astringent and for the treatment of pain and rheumatism [ 6 ]. Recent studies have shown that araticum pulp exerts various bioactivities, including antioxidant [ 7 , 8 , 9 ], anti-inflammatory [ 10 ], antibacterial [ 11 , 12 ], anti-Alzheimer’s [ 13 ], and anticancer effects [ 14 ]. These effects have been attributed to the presence of different bioactive phytochemicals that can be found in araticum pulp.…”
Section: Introductionmentioning
confidence: 99%
“…Aphandra natalia [17] Eugenia stipitata [32,[43][44][45][46][47][48][49][50]] Gustavia macarenensis [27,42,51] Mauritia flexuosa [21,25,41,44,47,52,53] Myrciaria dubia [46,[54][55][56][57][58] Oenocarpus bataua [26,27,59,60] Plukenetia volubilis [61][62][63][64][65] Pouteria caimito [47,66,67] Solanum quitoense [32,33,43,68,69] The results of this work are presented in three subsections: the first one shows an analysis of the use, origin, and location of the fruits in the Ecuadorian Amazon, responding to the objective of analyzing their ethnobotany in a preliminary way. In the Section 2, a brief description of the most studied Amazonian fruits in Ecuador was made, and their physicochemical characteristics were compiled, identifying their possible management.…”
Section: Fruits References Includedmentioning
confidence: 99%